Cak Nun, Maiyah, and Fandom: Participatory Culture Perspective (Journal of Advanced Research in Social Sciences, 2020)
The emergence of Maiyah in the midst of the downstream community marked a new format for recitation focusing on horizontal dialectics based on contextual themes. It can be said that Maiyah is a recitation forum that discusses actual themes such as culture, education, social, economy, religion, etc. by basing universal values such as egalitarian, democratic, and mutual respect. Maiyah has been held for about two decades and carried out in dozens of cities in Indonesia (Yogyakarta, Jakarta, Surabaya, Bandung, Semarang and others) and abroad (Hong Kong, Berlin, Philadelphia, Bangkok, Seoul, Amsterdam, Helsinki, London, and others). The communities which consist of a variety of backgrounds, both economic, class, age, and religion, have a strategic role in the discourse formation on what and how Maiyah is formulated. Such a tendency explains their position, if revealed from the fandom's perspective, it strengthens the relationship between Cak Nun and Maiyah. Cak Nun is widely known as a multidimensional human being: writer, intellectual, islamic scholar, and social activist. Cak Nun and Maiyah, therefore, are reciprocal correlates when viewed from the perspective of fandom. The fandom framework that emerged in the past decade and a half extends to the cyberspace. The emergence of new internet-based media requires the fandom movement in cyberspace. This article uses a fandom theory—Henry Jenkins—and particularly cultural participation perspective. Thus it could be answering the question of how stretching fandom is in the practice of Maiyah and how it appears to be related to the character of Cak Nun.